Porous Na3V2(PO4)3 prepared by freeze-drying method as high performance cathode for sodium-ion batteries. Issue 8 (1st June 2018) - Zheng, Li-Li; Xue, Yuan; Hao, Su-E.; Wang, Zhen-bo
Abstract: Na3 V2 (PO4 )3 has aroused extensive attention as next generation cathode material for sodium-ion batteries because of its abundance, good thermal stability and special 3D Na + channel. In the current work, porous Na3 V2 (PO4 )3 material is prepared by a simple freeze drying method followed by calcinations. Inside the porous material, Na3 V2 (PO4 )3 particles are embedded in carbon matrix, thus forming facial electron channels and reducing Na + ion diffusion distance at the same time. Benefiting from the special porous structure, this material displays excellent rate capability of 92.8 mA h g −1 at high rate of 20 C. Equally impressive is the long cycling stability. 90.2% of the initial capacity is retained after 2000 cycles at 5 C. This kind of feasible preparation method and beneficial design provide a good strategy for other materials to improve electric conductivity and cycling stability.